Muslim friendly tourism: developing and marketing MFT products and services in the OIC member countries - Ramli, Noriah (COMCEC Coordination Office, 2016)
The International Islamic University of Malaysia (IIUM) recognizes MFT as an integral part of the overall Malaysian Halal industry, a National Key Economic Area (NKEA) of the Economic Transformation Plan (ETP), and as an important factor in terms of its impact on the national GDP. IIUM has approached the Ministry of Education by submitting a proposal for developing the infrastructure for Muslim-friendly Hospitality services in Malaysia. Under the Niche Research Grant Scheme (NRGS), IIUM has been awarded a grant to develop a legal and administrative framework for Muslim-friendly Hospitality Services in Malaysia. This project has been awarded for five years (2012 to October 2018) resulting in a Technical Report and White Paper presentation to the government of Malaysia. This project is planned to be accomplished in three phases and has been divided into four project groups.223